2019
DOI: 10.1111/1365-2664.13429
|View full text |Cite
|
Sign up to set email alerts
|

Simulating nutrient release from parental carcasses increases the growth, biomass and genetic diversity of juvenile Atlantic salmon

Abstract: 1. The net transport of nutrients by migratory fish from oceans to inland spawning areas has decreased due to population declines and migration barriers. Restoration of nutrients to increasingly oligotrophic upland streams (that were historically salmon spawning areas) have shown short-term benefits for juvenile salmon, but the longer term consequences are little known. Here we simulated the deposition of a small number of adult Atlantic salmonSalmo salar carcasses at the end of the spawning period in five Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…As part of a larger study examining the ecological effects and evolutionary consequences of nutrient levels for freshwater ecosystems (Auer et al 2018a;McLennan et al 2019), we planted embryos from full-sibling Atlantic salmon families in equal distribution and density across 10 replicate tributary streams of the River Conon in northern Scotland (see app. A for description of study sites; apps.…”
Section: Introductionmentioning
confidence: 99%
“…As part of a larger study examining the ecological effects and evolutionary consequences of nutrient levels for freshwater ecosystems (Auer et al 2018a;McLennan et al 2019), we planted embryos from full-sibling Atlantic salmon families in equal distribution and density across 10 replicate tributary streams of the River Conon in northern Scotland (see app. A for description of study sites; apps.…”
Section: Introductionmentioning
confidence: 99%
“…Modelling by Benjamin et al (2020) has demonstrated the potential for this method with chinook salmon ( Oncorhynchus tshawytscha ), with increases in potential smolt output and size. However, in some cases faster growth may result in salmon reaching the size that triggers smolting a year earlier, at a smaller smolt size (McLennan et al, 2019). In such cases, nutrient additions may result in lower per capita chances of survival at sea, but increased numbers within a cohort surviving to become smolts, because of less time in the river and reduced inter‐cohort competition.…”
Section: Applying Science To Conservation and Managementmentioning
confidence: 99%
“…Although the populations of spawning migrants (and hence the nutrients transferred) tend nowadays to be on a larger scale in species of Pacific compared with Atlantic salmon, there is evidence that Atlantic salmon populations were once far larger, even before the declines documented over the last century (Lenders et al, 2016) so that their baseline ‘natural’ population size (and hence level of nutrient transfer) is unclear. Nonetheless, even current populations of Atlantic salmon are capable of delivering significant levels of marine‐derived nutrients to tributary streams, with positive impacts on algal growth, invertebrate populations and juvenile fish growth (Nislow, Armstrong & McKelvey, 2004; McLennan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Categorization and assessments of ES can be carried out to give an overview of a system, but are usually carried out in relation zones (Gende et al, 2002). Atlantic salmon are iteroparous, but between 20% and 100% of the adults nevertheless die after spawning (Nyqvist, 2016), and their carcasses may constitute a relevant nutrient addition for many rivers (McLennan et al, 2019). Moreover, during and after spawning, Atlantic salmon gametes are eaten by riverine organisms (Samways et al, 2017), also contributing to the linkage between the marine and freshwater ecosystems.…”
Section: Ecosystem Services Provided By Atlantic Salmon In Regulated ...mentioning
confidence: 99%